Burden of Culture-Confirmed Pediatric Pneumococcal Pneumonia in Latin America and the Caribbean: A Systematic Review and Meta-Analysis - Bardach, Ariel Esteban (2017)
Background: Pneumococcal pneumonia (PP) causes almost one in five deaths in children younger than 5 years worldwide. In Latin America and the Caribbean (LAC), pneumonia causes 14% of all deaths. Although pneumococcal disease is a vaccine-preventable disease that accounts for a significant proportion of this burden, the decision-making process to introduce pneumococcal conjugate vaccines in official schedules is still complex in LAC. Confirmed PP cases and epidemiology are the basis for broader projections. Objective: To gather all the information available in the LAC region to assist decision makers. Methods: We performed a systematic review of studies of consolidating and culture-confirmed pediatric PP in LAC (2000–2016) using a generic academic Internet search and search engines without language restrictions. Pairs of reviewers independently selected and assessed the studies’ methodological quality. We analyzed meta-information on pneumococcal serotypes available from the SIREVA laboratory-based surveillance system. Results: A total of 35 out of 750 initially identified studies were included. In the age group between 0 and 59 years, the incidence of culture-confirmed PP ranged from 10.2 to 43.0/100,000 children, with a pooled incidence of 20.4/100,000 children (95% confidence interval 0.0–123.2). Mortality ranged from 0.4 to 5.7/100,000 children, and the pooled mortality was 2.9/100,000 children (95% confidence interval 0.3–8.2). The pooled serotype distribution from surveillance data showed that serotypes 14, 1, and 6B were the most frequent serotypes in LAC, all included in licensed vaccines. Conclusions: Studies on confirmed pediatric PP were scarce in LAC in 2000 to 2016. Epidemiology indicators and health resource use are still poorly defined.